Avaliação do estado nutricional, consumo alimentar e segurança alimentar de pré-escolares: lentes para a promoção da saúde e prevenção da obesidade infantil - Bôto, Edilayne Gomes (2023)
The scenario of child poor nutrition, established by the nutritional transition in recent decades, with emphasis on overweight and obesity – possibly worsened by the COVID-19 pandemic – emerges as a major public health problem. This research aims to assess the nutritional status of preschoolers in the public educational system in Sobral, CE, and their relationship with food consumption in light of obesity associated factors. This is a quantitative, cross-sectional research, nested within a cluster- randomized clinical trial, carried out with 167 preschoolers and their respective guardians, from December 2022 to March 2023. To characterize nutritional status, the anthropometric technique was applied to generate the indicators of W/A, H/A, BMI/Age and waist circumference. Food consumption markers were used to define the association between food consumption and the use of electronic devices during meals. To map out the risk scenario regarding food security, the analysis was based on a screening survey form for food insecurity risks. The children mostly presented a nutritional status of eutrophy (55.69%), with the presence overweight risk (19.19%), overweight (9.58%), obesity (11.37%) and poor nutrition (4.19%). However, there is a higher prevalence of overweight and obesity in male children. Furthermore, 1.8% of children are very short for their age; 1.2% were moderately short for their age and 97.01% had adequate height for their age. Regarding the assessment of waist circumference, results indicate that 38.32% of children between 2-5 years old presented high values for this indicator, with greater emphasis on males (23.95%) with a p value < 0.05. As for food consumption, there was a considerable consumption of protein groups, fresh fruits, legumes, dairy,sandwich biscuits, candies, and soft drinks. However, it is worth noting that the group of instant noodles, snacks and chips, greens/vegetables, hamburgers and/or sausages, presented low consumption between children when compared to the other groups. With regard to the use of screens during meals, it was possible to identify that 67.65% of children used electronic devices while eating. In relation to the analysis of food and nutritional safety, it was possible to identify the presence of food and nutritional danger in over 40% of the surveyed children. It is noteworthy that height and weight had a direct correlation with nutritional status (r= 0.612 and p<001), and this analysis is replicated when evaluating the relationship between BMI and weight (r= 0.612 and p<001). The relationship between WC and weight indicates that the greater the child's weight, the higher the WC (r= 0.491 and p<001). Overweight and obesity can be observed in children under five years of age, with high rates of consumption of healthy food, and ultra-processed food as well. Simultaneously, children were in the habit of having their meals associated with digital technologies. Furthermore, food and nutritional danger was observed in the analyzed sample.